MEANING PARTICIPATION MASYARAKAT HUKUM ADAT DALAM PEMBENTUKAN PERATURAN DAERAH TENTANG RENCANA TATA RUANG WILAYAH - Riska Tri Utami (Universitas Borneo Tarakan, 2026)
This research aims to understand the meaning of community participation in customary law in the formation of regional regulations concerning spatial planning. Based on the background, two issues addressed in this research are the regulation of customary law communities in the formation of regional regulations concerning spatial planning in Tana Tidung Regency within the legal framework, and the meaning of participation of customary law communities in the formation of regional regulations regarding spatial planning. This research employs a normative legal research type, with the approach used being the statute approach. Based on the research findings, the existence of customary law communities is recognized in various regulations in Indonesia, including in the 1945 Constitution, Law Nomor 5 of 1960 concerning Basic Agrarian Regulations, Law Nomor 41 of 1999 concerning Forestry, Law Nomor 32 of 2009 concerning the Protection and Management of the Environment, the Minister of Home Affairs Regulation Nomor 52 of 2014, and Law Nomor 6 of 2014 concerning Villages. However, this recognition process requires commitment from both the central and regional governments, as well as active participation from the customary communities themselves. The legislation has provided a strong legal basis to protect their rights, but effective implementation still requires greater attention. Furthermore, the participation of customary law communities in the formation of regional regulations has profound meaning regarding the recognition of rights, sovereignty, and the preservation of their culture and environment. It is not just about formal inclusion in the legislative process, but also about providing space for the voices, values, and local wisdom that have shaped the lives of indigenous communities for centuries. By involving indigenous communities, local governments can produce fairer, more inclusive, and sustainable policies.